SIRI MARRIAGE PRACTICES IN MAKMUR VILLAGE COMMUNITY, IN GAMBUT, BANJAR DISTRICT - Rahmiyati, Rahmiyati; Rahmi, Diana; Nadiyah, Nadiyah (Universitas Islam Negeri Antasari Banjarmasin, 2020)
AbstractThis research is motivated by the existence of the practice of marriage series in the Makmur Village community, Gambut Banjar District, South Borneo. The procession of a marriage contract at a series of marriages conducted by the people of Makmur Village was carried out without the attendance of the Registrar of Marriage and the knowledge of the Religious Affairs Office (KUA). Even so, it turned out that after the marriage contract took place it was held at Siri marriage. This research is empirical legal research which is a case study, using a qualitative approach. The author delves into the data needed by conducting in-depth interviews with the subject under study. The findings of this study are that the marriage of Siri which is practiced by the people of Desa Makmur is held like the official marriage ceremony. Walimah was held openly by inviting family and surrounding communities. Holding a Siri marriage is an act that is usually done, therefore if Siri marriage is done continuously it will result in more siri marriages occurring in the community, especially in Makmur Village. AbstrakPenelitian ini dilatarbelakangi oleh adanya praktik walimah pernikahan siri pada masyarakat Desa Makmur Kecamatan Gambut Kabupaten Banjar. Prosesi akad nikah pada pernikahan siri yang dilakukan oleh masyarakat Desa Makmur dilaksanakan tanpa dihadiri oleh Pegawai Pencatat Nikah dan tanpa sepengetahuan pihak KUA. Meskipun begitu, ternyata setelah akad nikah berlangsung diadakanlah walimah pada pernikahan siri tersebut. Penelitian ini merupakan penelitian hukum empiris yang bersifat studi kasus, dengan menggunakan pendekatan kualitatif. Penulis menggali data yang diperlukan dengan melakukan wawancara mendalam terhadap subjek yang diteliti. Hasil temuan dari penelitian ini adalah walimah pernikahan siri yang dipraktikkan oleh masyarakat Desa Makmur diselenggarakan seperti walimah pernikahan yang resmi. Walimah tersebut diselenggarakan secara terang-terangan dengan mengundang keluarga dan masyarakat sekitar. Mengadakan walimah pernikahan siri merupakan suatu perbuatan yang sudah biasa dilakukan (kebiasaan), oleh karena itu apabila walimah pernikahan siri terus menerus dilakukan maka akan berakibat bertambah banyak terjadi pernikahan siri pada masyarakat, khususnya di Desa Makmur.